A new primitive polychaete with eyes from the lower Cambrian Guanshan biota of Yunnan Province, China - Zhao, Jun; Li, Yujing; Selden, Paul A. (Frontiers in Ecology and Evolution, 2023)
Annelids are abundant and speciose in modern world but comparatively few in the fossil record. Primitive annelids were expected to have developed eyes and nuchal organs, but until now definitive evidence is still lacking. Here, we describe Gaoloufangchaeta bifurcus gen. et sp. nov. from the Guanshan biota (Cambrian Series 2, Stage 3) of Yunnan Province, China. The overall profile of the body and the presence of tentacles and stout parapodia with simple chaetae establish it as a primitive polychaete. By bearing bicellular eyes and possible nuchal organs, the new form has developed relatively strong sensory abilities. Our material further confirms that polychaetes were already diverse by Cambrian Series 2, indicating a much earlier origin for the group.